EFEKTIVITAS STRATEGI BIMBINGAN TEISTIK UNTUK PENGEMBANGAN RELIGIUSITAS REMAJA (Penelitian Kuasi Eksperimen Terhadap Peserta Didik Kelas X SMA Nugraha Bandung Tahun Ajaran 2014/2015) - Dea Siti Ruhansih (QUANTA, 2017)
This research based on the low level of commitment in religion, who adhere to the religion but life has not been a truth values recommended in religion, or simply follow family tradition and friends without rationally as a principle. This study aimed to obtain the effectiveness theistic guidance strategy for developmental of teenagers religiosity in grade X of SMA Nugraha Bandung Academic Year 2014/2015. (1) describe the effectiveness of guidance theistic strategies for the development of religiosity (2) explain the dynamics of religiosity through  intervention theistic guidance strategies students of Grade X SMA Nugraha Bandung academic year 2014/2015. This research used a quantitative approach with quasi-experimental research with non-equivalent pretest-posttest control group design. Data was collected by religiosity questionnaires. Study participants were 18 people  in each of the experimental and control groups by using purposive sampling technique. The results showed is program interventions of theistic guidance strategies for the development of specific adolescent religiosity was effective to develop students  religiosity  on dimension religious believe, religious practice, religious experience and religious dimensions consequences. Theistic guidance strategies were not effective for the development of religious dimension of knowledge. The dynamics in religiosity through intervention theistic guidance strategies showed understanding in concept form at beliefe religious dimension, religious practices, and religious knowledge. The dynamics of behavior change interventions religiosity on theistic guidance strategies showed understanding of concepts and applications in everyday life on the religious dimension of religious experiences and consequences. The counselor suggested to understand scientific theistic.